2015
DOI: 10.1002/ppap.201500039
|View full text |Cite
|
Sign up to set email alerts
|

Direct Plasma Deposition of Lysozyme-Embedded Bio-Composite Thin Films

Abstract: Bio-composite coatings, consisting of an organic matrix embedding a bioactive molecule, have been deposited by means of atomizer-assisted atmospheric pressure plasma. Ethylene was chosen as the precursor of the matrix, while the atomizer was fed with a water solution of lysozyme. Coatings chemical composition was investigated by XPS, FTIR and MALDI-TOF spectroscopies, and it has been proved that the one-step inclusion of protein domains in the composite coatings is successful and lysozyme chemical structure is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 50 publications
2
62
0
1
Order By: Relevance
“…The plasma processing of materials including the amine plasma polymerization has gained considerable popularity for the development of bioactive materials, biosensors, antibacterial, and anti‐fungal surfaces . Various processes, monomers, and plasma reactors were employed to obtain the desired properties of the layers and several reviews reported the most prominent results achieved using allylamine, heptylamine, ethylenediamine, NH 3 , NH 3 /C 2 H 4 , and NH 3 /C 2 H 2 plasma polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma processing of materials including the amine plasma polymerization has gained considerable popularity for the development of bioactive materials, biosensors, antibacterial, and anti‐fungal surfaces . Various processes, monomers, and plasma reactors were employed to obtain the desired properties of the layers and several reviews reported the most prominent results achieved using allylamine, heptylamine, ethylenediamine, NH 3 , NH 3 /C 2 H 4 , and NH 3 /C 2 H 2 plasma polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…The MALDI spectra of native Lyz and of Lyz-embedded coatings were similar, only showing the mono- and bi-charged ions of lysozyme at m/z 14,300 and 7150, respectively, indicating that the protein was still intact in the coating after the deposition [82]. …”
Section: Plasma Deposited Composite Coatings Embedding Organic Antmentioning
confidence: 99%
“…This makes possible the deposition of hybrid multicomponent coatings in which for instance macromolecules (i.e., porphyrins, proteins, etc.) [27][28][29] or nanoparticles 25,26) are incorporated in a plasma-polymerized matrix. Recent studies have reported the preparation of organicinorganic nanocomposite coatings by using aerosol-assisted processes in which a dispersion containing preformed inorganic nanoparticles and the liquid precursor of the polymeric component is atomized and injected in aerosol form in an atmospheric pressure cold plasma.…”
Section: Aerosol-assisted Deposition Of Hydrocarbon Polymer/zno Nanopmentioning
confidence: 99%
“…1,2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Additionally, innovative deposition strategies have been developed, such as various aerosol-assisted processes [21][22][23][24] recently proposed for instance for the preparation of hybrid multicomponent coatings. [25][26][27][28][29] It has been demonstrated that DBD-based processes can afford the preparation of a wide range of coatings, spanning from the high quality dense inorganic layers (e.g., silica-like moisture barrier films 9,30) and hydrogenated silicon nitride layers for photovoltaics 31) ) obtained by diffuse DBDs, to the polymeric films characterized by superior retention of the monomer structure recently deposited using nanosecond pulsed DBDs. 32,33) Key concepts of atmospheric cold plasma deposition using DBDs are thoroughly discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%